A Case Study on Experiential Learning for Marketing Students - Taneja, Girish (Indian Journal of Marketing, 2016)
This study explained the need for experiential learning required in marketing curriculum and provides an example of "learning by doing" project developed for the students enrolled in professional selling, advertising, and consumer behavior courses. As a result of this project, students may have a better understanding of marketing concepts. In this project, selected students were imparted practical entrepreneurial training ; whereas, students of various marketing courses like professional selling, advertising, and consumer behavior as part of their evaluative assignment applied the theoretical concepts in the real scenario.